Penyusunan Instrumen Analisis Pedagogical Content Knowledge Guru IPA Madrasah Tsanawiyah Terintegrasi Konten Islami - Anggun Zuhaida (Edukasia Islamika, 2018)
An instrument for data collection needs to be analyzed before it is used in conducting research. The most pivotal characteristic of the instrument analysis exposes that researchers require to examine the validity and reliability. Pedagogical Content Knowledge (PCK) constitutes an academic construction that depicts an idea for stimulating individuals to learn. This present study aims to construct a PCK analysis-based research instrument for the natural science teachers of Islamic junior high schools, which is integrated with Islamic contents. A qualitative descriptive approach was employed in this study to explain the procedures for constructing the instrument. The procedures involved determining indicators, constructing a questionnaire as the research instrument, and measuring the validity, reliability, usability, and meaningfulness of the well-designed instrument. The research findings reveal that the development of the PCK analysis-based instrument dealt with three indicators, namely: knowledge of learners, knowledge of planning and designing, and knowledge of classroom instruction. Furthermore, the validity of the instrument demonstrated a positive result with minor revision, whereas the reliability with the Cronbach’s alpha coefficient showed that it was reliable. Meanwhile, considering the results of the usability and meaningfulness tests, it was attained that the PCK analysis-based instrument integrated with Islamic contents was commented at a very positive level.